Implementation of Cyber Notary in Electronic Deeds and Electronic Signatures Regarding Notary Positions - Rochmat, Adi Zaenur (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
Cyber notary is a concept that utilizes technological advances in carrying out the duties and authority of a notary. Document digitization is a challenge for notaries, especially related to document authentication and legalization, but Indonesia does not yet have specific rules regarding this matter, especially in the formation of electronic certificates and signatures. The purpose of this study was to determine and analyze the making of a notary deed electronically in terms of a cyber notary along with an electronic signature on the deed. This research is a juridical-normative research with descriptive analysis. The result of this research is that the making of an electronic deed is legal and binding as a notary deed even though the making of an electronic deed is not specifically regulated. The use of digital signatures can be done with the agreement of the parties as a simplification of business practices in Indonesia, especially in the implementation of mortgage rights.